2013 13th International Conference on Control, Automation and Systems (ICCAS 2013) 2013
DOI: 10.1109/iccas.2013.6704140
|View full text |Cite
|
Sign up to set email alerts
|

Trotting gait analysis of a lizard using motion capture

Abstract: Research into the gait planning of a walking robot is the underlying development of quadruped robots. Despite the efforts in stable gait planning, many walking robots that have been developed thus far do not have enough ability to adapt to uneven territory. In this paper, we acquired the motion data of the trotting lizards using the motion capture equipment and analyzed the gait systematically. In addition, we applied it to the kinematic model of the lizard and acquired the trajectory of each joint through an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…However, this strategy still has several technical obstacles, including high artificial expenses and expertise. Kim et al [17] proposed a spatially based joint gait and used it with lizard kinematics models after collecting data on lizard movement using infrared cameras. However, this strategy is currently only relevant to a single species, and trials for other animals must be developed to collect data.…”
Section: Introductionmentioning
confidence: 99%
“…However, this strategy still has several technical obstacles, including high artificial expenses and expertise. Kim et al [17] proposed a spatially based joint gait and used it with lizard kinematics models after collecting data on lizard movement using infrared cameras. However, this strategy is currently only relevant to a single species, and trials for other animals must be developed to collect data.…”
Section: Introductionmentioning
confidence: 99%
“…A lizard is a commonly seen reptile whose mechanics have been studied in detail in the following literature [3]. It was found that the walking and trotting gaits [4] exhibited by the lizards were similar to that of the mammals. The biomechanics and kinematics of the sprawling pattern exhibited by the lizards were studied extensively Supported by Tentacles Robotic Foundation.…”
Section: Introductionmentioning
confidence: 99%
“…The lizard-based bio-inspired robots have been made in the past, such as a water running robot [8], a leg mechanism [9], and a quadrupeds [10,11]. Motion analyis [12], motion planning [13], and gait planning [14] based on kinematics of the Gecko have been done on robotic lizards. A seven degrees of freedom robotic Gecko has been developed for the experimental verification of the kinematic analysis [15].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the lizard in particular, has been referred to as a biological model to locomote a mobile robot because of its advantage in multi-directional crawling with up to 24 [13] including climbing a vertical walls. For stable walking in straight, curved and inclined/declined path, the positions of supporting feet and position of center of gravity play an important role [14].…”
Section: Introductionmentioning
confidence: 99%